Minyak Astiri Bunga Mawar Untuk Menurunkan Nyeri Myogenic - Amalia Solichati Rizqi; Yudha Wahyu Putra; Dwi Wanito Ambarsari (Jurnal Ilmu Kesehatan Terpadu Indonesia, 2025)
Myogenic pain is a musculoskeletal complaint that arises from repetitive or excessive muscle activity and is commonly experienced by young adults. Rose essential oil (Rosa damascena) is known for its analgesic and anti-inflammatory properties. This study aimed to examine the effect of topically applied rose essential oil on increasing the pain threshold. The research employed a quantitative pre-experimental design using a one-group pretest-posttest approach. A total of 30 university students aged 19–24 years received an intervention in the form of topical application of rose essential oil to an area 7 cm distal to the m. epicondylus lateralis. Pain threshold was measured using faradic electrical stimulation. The results showed an increase in pain threshold from a mean of 8.4 mA to 12.1 mA after the intervention (p = 0.000). These findings indicate that rose essential oil is effective in reducing pain sensitivity and may be recommended as a complementary non-pharmacological therapy for myogenic pain. Its ease of use and safety make it suitable for community-based physiotherapy and self-care programs.